DEVELOPMENT OF A RULE-BASED SYSTEM FOR AUTOMATED BIM CODE-CHECKING - Di Giuda, Giuseppe Martino; Bonomi Boseggia, Andrea; Francesco, Paleari (Proceedings of International Structural Engineering and Construction, 2021)
This paper aims to describe a method for code-checking integrated into a BIM-based process. Recent developments in the field of model checking, made possible by the increased level of maturity of information modelling, open the possibility to facilitate regulatory controls. However, the automation of this process requires the definition and classification of rules, which represent the translation of regulatory requirements into a computer-based language. This activity, based on Italian legislation, represents the first step to propose a system that aims at integrating BIM models with the rule dataset. For this reason, this paper analyses the different types of queries through rules. These rules must recall principles of generality, replicability, consistency, uniformity. All these requirements are summarized in a structured spreadsheet and compared with the information contained in the BIM model, through a tool implemented within Dynamo software and facilitated by the use of scripts in Python language. The results of this process can be represented in the model and in the spreadsheet for an immediate visualization. This method allows a rapid and detailed control capable of highlighting the potential of information modelling and its integration.